BUFFER REPLACEMENT AND SIMULTANEOUS SACCHARIFICATION AND FERMENTATION ON BIOBUTANOL PRODUCTION?FROM LIGNOCELLULOSIC BIOMASS - Devitra Saka Rani; Yanni Kussuryani (Scientific Contributions Oil and Gas, 2016)
Lignocellulosic biomass is excellent feedstock for biofuel such as biobutanol. Bagasse, rice straw, and empty fruit bunch (EFB) oil palm are untapped potential for biobutanol production as gasoline blending/ substitution. However, biobutanol production by fermentation from lignocellulosic biomass is a process that consumes time and energy which leads to high production costs. This research is intended to optimize biobutanol production that reduces production costs, an important factor on an industrial scale. Optimization is conducted by replacing the buffer solution in enzymatic hydrolysis with distilled water and by using Simultaneous Saccharification and Fermentation (SSF). The results showed that the buffer replacement with distilled water can reduce cost by approximately 41,726 IDR/liter hydrolysate. Biobutanol contents from all biomass of bagasse, rice straw, and EFB oil palm are higher using SSF compared to Separate Hydrolysis and Fermentation (SHF). The SSF system can cut production time by 3 days and save electricity of 32.4 kWh.?